Melampaui Penanda Kebahasaan: Pencarian Mitos dalam Penafsiran Aḥmad bin ’Alī al-Būnī di Syams al-Ma’ārif al-Kubrā - Pratama, M. Hendrik (Contemporary Quran, 2023)
Mystical interpretations that are often seen as irrational interpretations obscure the rationality and scientific values contained in these interpretations. The assessment of mystical interpretation as irrational interpretation is caused by the understanding that someone who interprets mystically is thought to have no capability in interpreting the Qur’an. Thus, this study aims to demonstrate Aḥmad ibn ‘Alī al-Būnī’s mystical reasoning when interpreting the Qur’an in Shams al-Ma’ārif al-Kubrā from the argument that mystical interpretation-although seemingly irrational-has its own scientific basis and logical flow to arrive at a mystical understanding of the Qur’an. To achieve this goal, this study uses a qualitative method with the semiotic theory offered by Roland Barthes, which he divides into denotation and connotation analysis as a knife of analysis. The study shows that al-Būnī’s scientific background plays an important role in shaping his understanding of the Qur’anic verses. The interpretation of the basmalah, for example, al-Būnī interpreted it as a symbol of security, guarding, conquest, blessing, help, and salvation that resulted from his understanding of the names of the all-protective Allah contained in the term. The above understanding was formed through al-Būnī’s scientific background which mastered the science of letters (ilm al-huruf) and the names of Allah (al-Asma’ al-Husna). As a result, there are practices on the basmalah, such as reciting the basmalah 20 times before going to bed to avoid theft, demonic interference, or disaster.